PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN UMKM GALERI WONG KITO BERDASARKAN SAK EMKM - Maria, Maria; Choiruddin, Choiruddin; Satriawan, Indra; Wahyudi, Riza (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2023)
Gallery Wong Kito is engaged in the ecoprint creative industry that uses the natural color of leaves from various plants. This business is not only to meet the demands of the local market but its products to foreign countries, among others to the USA. Â . This business is not only to meet the demands of the local market but its products to foreign countries such as the USA. MSMEs Wong Kito needs a financial bookkeeping/reporting system to find out the results of their business operations. So far, Wong Kito Gallery has only recorded cash receipts and expenditures globally. For this reason, education and assistance in preparing financial statements are needed. The mentoring program uses a participatory approach starting from training, and recording transactions to the financial reporting stage.Â Financial statements made by business owners, evaluated and given input/suggestions if there is a mistake. The final result, the owner/manager of MSMEs Galeri Wong Kito can compile financial statements. Â